Vertigo and Dizziness in Childhood − Update on Diagnosis and Treatment - Jahn, K.; Langhagen, T.; Schroeder, A.S.; Heinen, F. (Neuropediatrics, 2011)
Vertigo and balance disorders are not uncommon in children. The prevalence of vestibular vertigo in 10-year-Dolds is estimated to be 5.7%. The most common cause is vestibular migraine which accounts for almost 40% of the diagnoses. In adolescents, the incidence of somatoform vertigo syndromes increases. Vestibular function can be reliably evaluated at the bedside by the head-impulse test for vestibulo-ocular reflex function, ocular motor testing of the central vestibular system, and balance tests for vestibulo-spinal function. Vestibular migraine is treated by behavioural and drug therapies. Somatoform vertigo improves if information about the disorder and behavioual advice are provided. Sometimes psychotherapy is useful; drug therapy is recommended in severe cases. Other common vestibular disorders in children include benign positioning nystagmus and labyrinthitis. In summary, the underlying causes of vertigo and dizziness in children can be diagnosed on the basis of patient history and clinical bedside testing. Reponses to caloric irrigation of the ears, rotational chair testing, posturography, and video-oculography can be used to ascertain the diagnosis. Brain imaging is indicated in patients presenting with subacute central vestibular signs. The majority of syndromes have a favourable prognosis and can be successfully treated.
Keywords: vertigo; balance; migraine; dizziness